Implementasi Kebijakan Kawasan Ekonomi Khusus Galang Batang Pulau Bintan Provinsi Kepulauan Riau - Nur Fajarriah Indah; Nilam Permata Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Special economic zones as a tool for regional economic development are important because they contribute to reducing disparities between regions and reducing poverty in a fair and consistent manner. In developing Special economic zones , it is important to carry out coordinated planning between sectors so that sustainable development is part of national development. This research focuses on the impact of special economic zone policies in Indonesia. The type of research is normative legal research, which includes documents that are used as references, especially basic legal documents, and secondary documents such as literature, books, scientific works, articles scientific, etc., where the analysis is carried out in more depth related to the problem of studying legal provisions. This document discusses Special Economic Zones in Indonesia and their policies. The Galang Batang SEZ was developed as an industrial center for the processing of mining minerals such as bauxite and its derivative products. The synergistic impacts of SEZs include: Increasing Gross Regional Domestic Product SEZs can increase economic activity in a region cumulatively, which contributes to increasing regional GDP and Infrastructure Development: SEZs are National Strategy Projects that are supported by the development of surrounding infrastructure.